Assessment of the sensory quality and shelf stability of selected Horro beef muscles in Ethiopia - Yadata, M.A.; Werner, Christian R.; Tibbo, Markos; Wollny, C.B.A.; Wicke, M. (Elsevier, 2009)
The objective of this work was to assess sensory quality and retail life of Horro beef muscles in Ethiopia. Six muscles: M. rhomboideus (RM), M. infraspinatus (IS), M. longissimus lumborum (LL), M. semimembranosus (SM), M. biceps femoris (BF) and M. rectus femoris (RF) were considered. Sensory quality of the muscles was rated by a 9-member trained panel for palatability, tenderness, juiciness, amount of connective tissue (ACT), lean color and surface discoloration and measured by Warner-Bratzler Shear Force (WBSF). Retail life of the six muscles were evaluated for CIE 1976 L*a*b* color values across 6 days. Significant differences (p < 0.05) between muscles for all sensory attributes and WBSF were found. Significant L*a*b* color values of muscles and USDA quality grades by retail life were found (p < 0.05). Significant correlations (p < 0.05 or p < 0.01) of key parameters were also identified.